2014
DOI: 10.1371/journal.pone.0104837
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Analysis of 48 Type 2 Diabetes Genetic Risk Variants Shows No Discriminative Value to Predict Time to First Prescription of a Glucose Lowering Drug in Danish Patients with Screen Detected Type 2 Diabetes

Abstract: ObjectiveTo investigate the genetic influence of 48 type 2 diabetes susceptibility variants on disease progression measured as risk of early prescription redemption of glucose lowering drugs in screen-detected patients with type 2 diabetes.MethodsWe studied type 2 diabetes progression in 1,480 patients with screen-detected type 2 diabetes from the ADDITION-Denmark study using information of redeemed prescriptions from the Register of Medicinal Products Statistics from 2001–2009 in Denmark. Patients were cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In this study, incident cases were randomized into two intervention groups: a conventional group where the individual received usual care as per national guidelines, and the other which received intensified multifactorial intervention group with lifestyle counselling and additional management for blood pressure and cholesterol. While the overall PRS did not impact on diabetes progression, a sub‐PRS that incorporated only diabetes risk variants linked with insulin resistance showed association with time to insulin prescription (HR 1.39 (95% CI 1.09‐1.77)) in the intensified intervention group …”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In this study, incident cases were randomized into two intervention groups: a conventional group where the individual received usual care as per national guidelines, and the other which received intensified multifactorial intervention group with lifestyle counselling and additional management for blood pressure and cholesterol. While the overall PRS did not impact on diabetes progression, a sub‐PRS that incorporated only diabetes risk variants linked with insulin resistance showed association with time to insulin prescription (HR 1.39 (95% CI 1.09‐1.77)) in the intensified intervention group …”
Section: Resultsmentioning
confidence: 89%
“…From the 61 included articles, 56 studies assessed the phenotypic factors affecting diabetes progression, while only four studies investigated genotypic determinants of diabetes progression and one study assessed both phenotypic and genotypic factors . Before 2000, there were only four studies published and between 2000 and 2010; there were 20 studies published, with the remaining 37 studies published after 2010.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a recent Danish study, carried out in a population‐based cohort predominantly treated with MET (55%), has investigated the influence of 48 T2DM susceptibility variants on disease progression assessed as early redemption of either a glucose‐lowering drug or an insulin drug prescription. Results have shown that common T2DM‐associated gene variants do not significantly affect disease progression requiring additional therapies …”
Section: Discussionmentioning
confidence: 99%